1988
DOI: 10.1016/0735-1097(88)92615-0
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilator and inotropic drugs for the treatment of chronic heart failure: Distinguishing hype from hope

Abstract: During the past 10 years, more than 80 orally active vasodilator and inotropic agents have been tested in the clinical setting to evaluate their potential utility in the treatment of chronic heart failure. Although the initial reports of all of these drugs suggested that each represented a major therapeutic advance, only three agents--digoxin, captopril and enalapril--have produced consistent long-term hemodynamic and clinical benefits in these severely ill patients. Most of the other drugs that have been test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(27 citation statements)
references
References 175 publications
0
26
0
1
Order By: Relevance
“…Although some studies have demonstrated that acute haemodynamic changes in response to drug therapy are poor predictors of long-term clinical outcomes [1,2] , it has been suggested that serial measurements, rather than isolated 'snapshots', might provide unique insight regarding pathophysiological mechanisms and responses to treatment. Other studies of titration of vasodilator dosage according to haemodynamic end-points have demonstrated important clinical improvements that may not have been possible when simply using an empirical target dose [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have demonstrated that acute haemodynamic changes in response to drug therapy are poor predictors of long-term clinical outcomes [1,2] , it has been suggested that serial measurements, rather than isolated 'snapshots', might provide unique insight regarding pathophysiological mechanisms and responses to treatment. Other studies of titration of vasodilator dosage according to haemodynamic end-points have demonstrated important clinical improvements that may not have been possible when simply using an empirical target dose [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…A variety of therapeutic strategies have been applied to augment the depressed left ventricular function of heart failure, particularly during periods of acute decompensation (Packer, 1988;Rahimtoola, 1989;Shipley and Hess, 1995). Current clinically available inotropic agents that act via elevation of cyclic AMP, such as dobutamine and phosphodiesterase inhibitors; are associated with tachycardia, significant changes in preload or afterload or increases in myocardial O 2 consumption (MVO 2 ), and decreases in myocardial mechanical efficiency (Katz, 1986;Simaan et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of left atrial pacing at a constant heart rate and at matched contractile work, MVO 2 was increased by LY341311 to the same extent as dobutamine. These data indicate that autonomically mediated bradycardia produced by LY341311 contributes to a favorable net metabolic effect on myocardial O 2 utilization in the failing heart while providing inotropic support comparable to a ␤-receptor-mediated agonist.A variety of therapeutic strategies have been applied to augment the depressed left ventricular function of heart failure, particularly during periods of acute decompensation (Packer, 1988;Rahimtoola, 1989;Shipley and Hess, 1995). Current clinically available inotropic agents that act via elevation of cyclic AMP, such as dobutamine and phosphodiesterase inhibitors; are associated with tachycardia, significant changes in preload or afterload or increases in myocardial O 2 consumption (MVO 2 ), and decreases in myocardial mechanical efficiency (Katz, 1986;Simaan et al, 1988).…”
mentioning
confidence: 99%
“…Phases 2, 3, and 4-Efficacy periods. Phases [2][3][4] consisted of three identical double-blinded, study drug administration periods lasting for 8 weeks each. The study was designed for each patient to cross over to a different study drug treatment regimen every 8 weeks so that by the end of the study, all patients would have received all three treatment regimens in a random fashion.…”
Section: Study Protocolmentioning
confidence: 99%